2014
DOI: 10.1016/j.cis.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Emerging methods for the fabrication of polymer capsules

Abstract: Hollow polymer capsules are attracting increasing research interest due to their potential application as drug delivery vectors, sensors, biomimetic nano- or multi-compartment reactors and catalysts. Thus, significant effort has been directed toward tuning their size, composition, morphology, and functionality to further their application. In this review, we provide an overview of emerging techniques for the fabrication of polymer capsules, encompassing: self-assembly, layer-by-layer assembly, single-step poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
178
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(182 citation statements)
references
References 295 publications
(230 reference statements)
4
178
0
Order By: Relevance
“…This is the main reason why cargo is lost during the fabrication of capsules using the co-precipitation method. There are also other ways of synthesizing capsules, apart from the LbL method and the reader is referred to recent reviews on capsules as biological carriers for further information [4,11,12]. The capsule wall represents a semipermeable membrane, as small molecules can diffuse almost freely through the pores [13], whereas large molecules, for example dextran molecules or proteins, cannot pass the capsule walls.…”
Section: Polyelectrolyte Multilayer Capsulesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the main reason why cargo is lost during the fabrication of capsules using the co-precipitation method. There are also other ways of synthesizing capsules, apart from the LbL method and the reader is referred to recent reviews on capsules as biological carriers for further information [4,11,12]. The capsule wall represents a semipermeable membrane, as small molecules can diffuse almost freely through the pores [13], whereas large molecules, for example dextran molecules or proteins, cannot pass the capsule walls.…”
Section: Polyelectrolyte Multilayer Capsulesmentioning
confidence: 99%
“…non-spherical calcium carbonate cores, and showed that the resulting capsules kept the form of the templates after their removal [3]. Different materials, such as polystyrene, silica or calcium carbonate have been used to fabricate capsule cores [4], but even red blood cells or Escherichia coli can be used [5,6]. With the right choice of template the capsules can be tuned in size from 30 nm up to several microns, opening the way for customization of the capsules according to the problem of interest [4].…”
Section: Polyelectrolyte Multilayer Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of light sensitive chromophores like azo-groups, or a redox ferrocene (Fc) moiety, and pH-sensitive dansyl residues, or a benzyl moiety allowed to control CDs conjugates by temperature and obtained stimuli-responsive switching sol-gel systems [311]. The reversible association/dissociation of the polymer Moreover, pH-responsive capsules [289,290] linked with glutamic acid residues and containing disulfide groups within the shell or on the surface of polymeric capsules can be gathered into endosomes. The disulfide acts as a linker to attach different functional moieties to the surface of polymer capsules via a covalent or noncovalent interaction.…”
Section: Stimulus Responsive Shell-tuning Capsules For Drug Deliverymentioning
confidence: 99%
“…5 Deposition of polymer films onto the surface of colloidal core templates via the layerby-layer (LbL) technique and subsequent removal of the cores is the most effective approach to fabricate polymer hollow capsules with a uniform size and controlled film thickness. 6 Here, appropriately selecting the core template used and the template removal process is important for successfully fabricating hollow structures with a well-defined morphology.…”
mentioning
confidence: 99%